PENGARUH KECERDASAN EMOSIONAL DAN STRES KERJA TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI SEBAGAI VARIABEL MODERASI (STUDI PADA KANTOR KESYAHBANDARAN UTAMA BELAWAN) - Yan rizal (Universitas Islam Islam Sumatera Utara, 2020)
The formulation of problem in this research there is influence of emotional intelligence on motivation. There is influence of job stress on motivation. There is emotional intelligence on employees performance. There is job stress on employees performance. There is motivation on employees performance. The purpose of this research is for know influence and analize of emotional intelligence on motivation. For know influence and analize of job stress on motivation. For know influence and analize of emotional intelligence on employees performance. For know influence and analize of job stress on employees performance. For know influence and analize of motivation on employees performance. The sample in this research is 60 employees, with data analysis technique used is descriptive analysis and multiple linear regression analysis. The research result is emotional intelligence variable influence positive and don’t significant on motivation. Job stress variable influence negative and don’t significant on motivation. Emotional intelligence variable influence positive and significant on employees performance. Job stress variable influence positive and significant on employees performance. Motivation variable influence negative and don’t significant on employees performance. Emotional intelligence and job stress variable influence positive and significant on employees performance with motivation as moderasi variable